Complex patterns in tolerance and resistance to pests and diseases underpin the domestication of tomato. Issue 1 (31st December 2019) - Ferrero, Victoria; Baeten, Lander; Blanco‐Sánchez, Lidia; Planelló, Rosario; Díaz‐Pendón, Juan Antonio; Rodríguez‐Echeverría, Susana; Haegeman, Annelies; de la Peña, Eduardo
Summary: A frequent hypothesis explaining the high susceptibility of many crops to pests and diseases is that, in the process of domestication, crops have lost defensive genes and traits against pests and diseases. Ecological theory predicts trade‐offs whereby resistance and tolerance go at the cost of each other. We used wild relatives, early domesticated varieties, traditional local landraces and cultivars of tomato ( Solanum lycopersicum ) to test whether resistance and tolerance trade‐offs were phylogenetically structured or varied according to degree of domestication. We exposed tomato genotypes to the aphid Macrosiphum euphorbiae, the cotton leafworm Spodoptera littoralis, the root knot nematode Meloidogyne incognita and two common insect‐transmitted plant viruses, and reconstructed their phylogenetic relationships using Genotyping‐by‐Sequencing. We found differences in the performance and effect of pest and diseases but such differences were not related with domestication degree nor genetic relatedness, which probably underlie a complex genetic basis for resistance and indicate that resistance traits appeared at different stages and in unrelated genetic lineages. Still, wild and early domesticated accessions showed greater resistance to aphids and tolerance to caterpillars, nematodes and diseases than modern cultivars. Our findings help to understand how domestication affects plant–pest interactions and underline the importance of tolerance in crop breeding.